Elizabeth - Kapur, Shekhar 1945-; Owen, Alison; Fellner, Eric; Bevan, Tim (PolyGram Video, 1998)
Queen Elizabeth I must learn to weigh her counsel carefully and ignore her private yearnings if she is to keep her crown--and her head. A thriller of intrigue in the court of one of history's greatest monarchs.